Protective Effects of Alstonia scholaris (L.) R.Br. Bark Extract against Oxidative Stress Induced By Hydrogen Peroxide - Hussain, Anowar; Gogoi, Bhaskarjyoti; Ramteke, Anand (Pharmacognosy Communications)
Objective: To evaluate the protective effects of bark extract of Alstonia scholaris (L.) R.Br. against oxidative stress induced by hydrogen peroxide (H 2 O 2). Materials and Methods: Study was carried out in isolated lymphocytes cultured in vitro. Lymphocytes were treated with extract or extract + H 2 O 2 and the level of reduced glutathione (GSH) and nitric oxide (NO) as well as the activity of lactate dehydrogenase (LDH) were measured. Results: Treatment of lymphocytes with bark extract modulated the levels of GSH and NO with decreased LDH activity. Pretreatment with bark extract also signifi cantly increased the level of GSH in lymphocytes treated with 1% H 2 O 2. But, the levels of NO and LDH activity were decreased for similar treatment condition. Conclusion: The present data suggests that the protective effects of bark extract may be via up regulation of GSH and down regulation of NO levels. The modulation of GSH levels in the lymphocytes might be due to the phytochemicals present in the hydro-alcoholic extract of Alstonia scholaris.
Keywords: Alstonia scholaris; hydrogen peroxide; Lactate dehydrogenas; nitric oxide; reduced glutathione